Educational Internationalism in the Cold War : Plural Visions, Global Experiences - Damiano Matasci; Raphaëlle Ruppen Coutaz (Routledge, 2025)
This edited volume delves into the intricate landscape of educational internationalism during the Cold War, providing an in-depth examination of its diverse forms, impulses, and global impacts.Through multilingual archival research, the chapters uncover a variety of experiences that have fostered cross-border exchanges and cooperation within, between, and beyond the Western and Eastern blocs. Promoted by a wide range of individual and collective actors, internationalism in education has extended across a broad spectrum of fields, including academic mobility schemes, cultural interchanges, youth science competitions, development programs, and training courses. This collection offers, for the first time, a comprehensive analysis of these initiatives, revealing their intersections with national educational policies and processes of decolonization, development, and Europeanization. It also challenges conventional historical narratives by both uncovering forms of collaboration and solidarity that transcended the Iron Curtain and emphasizing the pivotal role of the Global South as a central arena of encounters.Educational Internationalism in the Cold War presents a rich understanding of the Cold War as a laboratory of contemporary globalization and is a valuable addition to the scholarship on one of the most critical moments of the twentieth century.